Pengaruh Earning Per Share , Return On Equity Dan Return On Asset Terhadap Harga Saham - Subur Permana; Suherdi Suherdi; Edi Ruslani (E-Journal Studia Manajemen, 2022)
This study aims to obtain information relating to factors that influence stock prices in real estate companies and construction in 2017 on the Indonesian stock exchange 2017. The population used was 555 companies with 85 samples taken by random sampling . The method in this study is descriptive quantitative. The results show that: l) There is no effect ofprice earnings ratio on stock prices. An increase in positive price earnings ratio will not increase the stock price, 2) There is a positive direct effect of earnings per share on stock prices. Increased earnings per share will affect the increase in stock prices. 3) There is no gf./&ct Qfdebt to equity ratio on stock prices. The increase in debt to equity ratio will not affect the increase in stock prices. 4) There is no effect Q/net income on stock prices. The increase in net prQ/it will not qffect the increase in stock prices, 5) There is a positive direct positive effect between price ratio, earnings per share, debt to equity ratio, and net prQ/it on stock prices Price erosion ratio, earnings per share, debt to equity ratio, and net profit will affect the increase in stock prices. For this reason, investors should be more observant fundamentally looking at price earning ratios, earnings per share, debt to equity ratio and net income. Which component is thought to be supportive and stronger influences, that must be seen clearly, so that in choosing stock prices can he done appropriately. Fundamentally these data are presented clearly in the issuers report that is usually reported once in a year, for long-term investors, the factors that affect the price Q/ the stock move simultaneously, let it be seen also other components of each of these variables . For example, bias can be readfrom the mathematical formula that exists from each of these variables. For short-term investors, you should use the technical analysis as a basic reference, measure and choose which stocks are worth buying, using a trend analysis (trand), but PER, EPS, DER and net profit can also be seen as a second opinion